Increased PUFA levels in kidney epithelial cells in the course of diclofenac toxicity. (August 2020) - Aslan, Mutay; Kırımlıoğlu, Esma; Afşar, Ebru; Çeker, Tuğçe; Yılmaz, Çağatay
Abstract: This study evaluated polyunsaturated fatty acids (PUFAs) in human kidney epithelial cells exposed to diclofenac (DCL) toxicity. Kidney cells were treated with DCL to induce cytotoxicity and thymoquinone (TQ) was administered to decrease cytotoxic effects. Levels of arachidonic acid (AA, C20:4n-6), dihomo-gamma-linolenic acid (DGLA, C20:3n-6), eicosapentaenoic acid (EPA, C20:5n-3) and docosahexaenoic acid (DHA, C22:6n-3) were determined by liquid chromatography coupled with tandem mass spectrometry. Cytosolic phospholipase A2 (cPLA2 ), cyclooxygenase 1 (COX-1) and prostaglandin E2 (PGE2 ) were measured to evaluate changes in enzyme activity. Immunofluorescence staining and western blot analysis was performed to determine protein levels of COX- 1. Renal cell toxicity was accomplished by DCL and was alleviated by TQ treatment. Diclofenac significantly increased all measured PUFAs while pretreatment with TQ decreased PUFA levels in DCL treated cells. Cytosolic PLA2 and total COX activity was significantly decreased in DCL treated cells. Immunofluorescence staining and western blot analysis confirmed significantly decreased COX-1 levels in DCL and DCL + TQ treated groups. The results of this study reveal that DCL treatment is associated with accumulation of PUFAs in kidney cells. We suggest that PUFA accumulation in DCL toxicity might be a consequence of both cPLA2 and COX-1 inhibition. Thymoquinone administration, along with DCL treatment alleviated the buildup of PUFAs and DCL-induced cell death in kidney cells. Highlights: Diclofenac (DCL) toxicity causes polyunsaturated fatty acid (PUFA) accumulation in kidney cells. PUFA accumulation in DCL toxicity is associated with cytosolic phospholipase A2 inhibition PUFA accumulation in DCL toxicity is associated with cyclooxygenase 1 inhibition Thymoquinone attenuates diclofenac-induced PUFA accumulation.